Emerging Forms of Precariousness Related to Autonomy at Work: Toward an Empirical Typology - Florin, Louis; Pichault, François (Frontiers in Sociology, 2020)
Societal, technological and economical changes in the last decades have led to the development of new work arrangements located in a « grey zone » between standard employment and classical self-employment (Cappelli & Keller, 2013a; ILO, 2016; Katz & Krueger, 2016). Official labour market statistics must be adapted to provide researchers and policymakers with relevant data on this population (Gazier et al., 2016; National Academy of Sciences, Engineering and Medicine, 2017; ILO, 2018). Cappelli & Keller (2013b) point out that new work arrangements are characterized by changes in the management of the work relationships (with a growing intervention of labour market intermediaries) and in the way the work is supervised (from work processes to outcomes). The concept of autonomy thus becomes a central feature of new work arrangements leading to specific configurations of risks and opportunities for individual workers concerned. Autonomy can be divided in three main dimensions: work status, work content and working conditions (Pichault & McKeown, 2019). International surveys such as the European Working Conditions Survey (EWCS) provide valuable data covering these dimensions of autonomy. Our paper is focused on a specific category of workers experiencing the ambiguities of autonomy at work: Independent Professionals (Ipros). Ipros provide various forms of intellectual work in the service sector through self-employment and are often regarded as a highly autonomous workforce (Leighton & Brown, 2014; McKeown, 2015) while they can also be subject to precarious situations regarding their economic dependency or freedom of choice (de Peuter, 2011; Standing, 2011; Bergvall-Kåreborn & Howcroft, 2013). The objectives of this paper are, first, to build a set of indicators likely to measure the various dimensions of autonomy, and, second, to provide an empirical typology of new work arrangements by using cluster analysis methods. Through the application of this analytical framework on the EWCS 2015 data, we observe various situations in terms of risk and opportunities related to autonomy, shedding light on unexpected precarious situations where Ipros face the risks of autonomy without getting the associated benefits. Our results provide a nuanced typology of empirical situations, overcoming such a dichotomic vision of nonstandard work arrangements.